A review of bioregulatory and coupled mechanobioregulatory mathematical models for secondary fracture healing. (October 2017) - Wang, Monan; Yang, Ning
Highlights: We review the importance of biochemical signals and its mathematical modeling in bone fracture healing. Biochemical signals are regulatory factors during healing process. Mathematical models contribute to our understanding of basic physiological and pathological fracture healing. Mathematical models show their potential to the clinical application. Abstract: Fracture healing is a complex biological process involving many cellular and molecular events. During fracture healing, biochemical signals play a regulatory role in promoting the healing process. Although many experiments have been conducted to study fracture healing, not all of the mechanisms are clearly understood. Over the past years, a lot of mathematical models and computational simulations have been established to investigate the fracture healing process. These models offer a powerful tool to study the interplay between cell behaviour, mechanical stimuli and biochemical signals and help design new treatment strategies. However, most of the mathematical models focus on the effect of mechanical stimuli and few models consider the important role of biochemical signals during fracture healing. In this review, we first emphasize the importance of biochemical signals during fracture healing. Then, existing bioregulatory and coupled mechanobioregulatory models are presented. Finally, some limitations and possible solutions are discussed.